Natural Vegetation of Mountainous Environments: Morraria do Urucum and Serra do Amolar, Pantanal, Brazil (Terr@ Plural, 2023)
Mountainous environments are considered unique habitats with distinct ecosystem characteristics. Therefore, more studies must understand and characterize these habitats to improve their preservation. Therefore, this paper aims to characterize two mountainous areas in Central Brazil, Morraria do Urucum and Serra do Amolar to address a discussion about the ‘Campos de Altitude’ (altitude grasslands) vegetation above 700 m altitude. Differently from Serra do Amolar, Morraria do Urucum does not have Conservation Units in its territory, raising concerns related to its preservation. Actions are urgent to prevent the loss of mountainous biodiversity, but these must reflect ecological properties and successional processes and, therefore, allow adequatemanagement practices.
Keywords: Mountainous Ecosystems; Wetlands; Conservation; Altitude Grasslands